2020
DOI: 10.3390/ijerph17228701
|View full text |Cite
|
Sign up to set email alerts
|

Social Bots’ Sentiment Engagement in Health Emergencies: A Topic-Based Analysis of the COVID-19 Pandemic Discussions on Twitter

Abstract: During the COVID-19 pandemic, when individuals were confronted with social distancing, social media served as a significant platform for expressing feelings and seeking emotional support. However, a group of automated actors known as social bots have been found to coexist with human users in discussions regarding the coronavirus crisis, which may pose threats to public health. To figure out how these actors distorted public opinion and sentiment expressions in the outbreak, this study selected three critical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 86 publications
(132 reference statements)
3
44
2
Order By: Relevance
“…Here we have shown that a majority of known bots are tweeting about COVID-19, a finding that corroborates similar studies [ 68 , 70 ]. Early in the pandemic, one study found that 45% of COVID-19related tweets originate from bots [ 71 ], although Twitter has pushed back on this claim, citing false-positive detection algorithms [ 72 ].…”
Section: Implications For the Covid-19 Pandemicsupporting
confidence: 92%
“…Here we have shown that a majority of known bots are tweeting about COVID-19, a finding that corroborates similar studies [ 68 , 70 ]. Early in the pandemic, one study found that 45% of COVID-19related tweets originate from bots [ 71 ], although Twitter has pushed back on this claim, citing false-positive detection algorithms [ 72 ].…”
Section: Implications For the Covid-19 Pandemicsupporting
confidence: 92%
“…Here we have shown that a majority of known bots are tweeting about COVID-19, a finding that corroborates similar studies [68,70]. Early in the pandemic, one study found that 45% of COVID-19-related tweets originate from bots [71], although Twitter has pushed back on this claim, citing false-positive detection algorithms [72].…”
Section: Implications For the Covid-19 Pandemicsupporting
confidence: 89%
“…It is also possible that nonhuman Twitter users (bots) were represented in our sample. Previous research has found that Twitter bots have manipulated public opinion and fueled cascades of negative emotions related to topics about COVID-19 [ 34 ]. Without any way to systematically identify and exclude these tweets, we suspect that several such tweets were included in our analysis.…”
Section: Discussionmentioning
confidence: 99%